Sadiria yingjiangensis (Myrsinoideae, Primulaceae), a new species reported from West Yunnan, China - Wang, Ze-Huan; Wang, Li-Yan; Li, Rong-Jia; Peng, Hua (Phytotaxa, 2019)
Sadiria yingjiangensis from West Yunnan, China, is described as a species new to science and illustrated here. It morphologically resembles S. longistyla, but differs in the number of leaves clustered on the plant apex, the shape of inflorescences and the ratio of the length of sepals to petals.